2024
DOI: 10.1021/acsami.4c01525
|View full text |Cite
|
Sign up to set email alerts
|

Layered Sn–Au Thin Films for Increased Electrochemical ATR-SEIRAS Enhancement

Yuval Fishler,
Noemi Leick,
Glenn Teeter
et al.

Abstract: Operando electrochemical attenuated total reflection surface-enhanced infrared absorption spectroscopy (EC ATR-SEIRAS) is a valuable method for a fundamental understanding of electrochemical interfaces under real operating conditions. The applicability of this method depends on the ability to tune the optical and catalytic properties of an electrode film, and it thus requires unique optimization for any given material. Motivated by the growing interest in Sn-based electrocatalysts for selective reduction of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…With some degree of understanding of what might be present on the surface during CO 2 R from the GC-DFT analysis described above, we performed ATR-SEIRAS experiments to validate and refine this understanding. We previously reported a method to prepare both fully metallic and oxidized SEIRAS-active Sn films, which we used in the present study to discern differences in adsorbed species during CO 2 R . Before we begin the discussion of the SEIRAS results, we would like to point out that ex situ characterization of the two Sn films after the reductive treatment shows that they have similar degrees of oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With some degree of understanding of what might be present on the surface during CO 2 R from the GC-DFT analysis described above, we performed ATR-SEIRAS experiments to validate and refine this understanding. We previously reported a method to prepare both fully metallic and oxidized SEIRAS-active Sn films, which we used in the present study to discern differences in adsorbed species during CO 2 R . Before we begin the discussion of the SEIRAS results, we would like to point out that ex situ characterization of the two Sn films after the reductive treatment shows that they have similar degrees of oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…With some degree of understanding of what might be present on the surface during CO 2 R from the GC-DFT analysis described above, we performed ATR-SEIRAS experiments to validate and refine this understanding. We previously reported a method to prepare both fully metallic and oxidized SEIRAS-active Sn films, which we used in the present study to discern differences in adsorbed species during CO 2 R. 32 Before we begin the discussion of the SEIRAS results, we would like to point out that ex situ characterization of the two Sn films after the reductive treatment shows that they have similar degrees of oxidation. Both Sn films undergo spontaneous oxidation in air, which complicates the assignment of the exact oxidation state of the two films during CO 2 R. Dutta et al performed operando EXAFS experiments on SnO 2 -based catalysts and found that metallic Sn coordination was not observed until −0.88 V RHE , and SnO 2 and SnO features were still observed even at −1 V RHE .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations